Analysis Of The Effect Of Distance Between User Equipment and eNodeB On Rsrp And Sinr Value In 1800 Mhz Lte Technology - Afrizal Yuhanef; Dikky Chandra; Bintan Thaibah; Herry Setiawan (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
Technological progress is currently experiencing very rapid development where mobile communication systems are technologies that support seamless communication links. When the user equipment is within range of the eNodeB, factors such as the distance between the user equipment and the eNodeB will affect the signal performance received by the user equipment. In this study, we analyzed the effect of the distance between user equipment and eNodeB on RSRP and SINR values on LTE 1800 MHz technology. The method used is the measurement of the drive test and the calculation of the Link Budget and the Propagation Model. The results and analysis show irregular changes in RSRP and SINR values caused by varying obstacle factors in the propagation environment. According to the calculation results of the Link Budget and the Propagation Model on the research object, it was found that the RSRP and SINR values decreased for every 100 m change in distance from the eNodeB. Based on the comparison, it is obtained that the PCS Extension to Hatta propagation model is close to the drive test measurement results.